Adjunctive dental therapies in caries-active children: Shifting the cariogenic salivary microbiome from dysbiosis towards non-cariogenic health. (December 2020) - Lyashenko, Claudia; Herrman, Elisa; Irwin, Jessica; James, Allie; Strauss, Shay; Warner, John; Khor, Brandon; Snow, Michael; Ortiz, Stephanie; Waid, Erin; Nasry, Bishoy; Chai, Jennifer; et al.
Abstract: Background: The oral microbiome is a complex assembly of microbial species, whose constituents can tilt the balance towards progression of oral disease or sustained health. Recently we identified sex-specific differences in the salivary microbiome contained within caries-active and caries-free children. In this study, we sought to ascertain if adjunctive dental therapies, including povidone iodine and chlorhexidine, were effective in shifting the cariogenic microbiome from dysbiosis to non-cariogenic health. Design: We recruited young children (ages 2–12 years) to enter five enrollment groups, with each group (N = 9–30 participants/group) receiving caries restorative and/or adjunctive therapies, either singularly or in combination (OHSU IRB #6535). Saliva specimens were collected pre- and post-treatment (4–8 weeks) of caries preventive measures, and oral microbiota were identified using next generation sequencing (HOMI NGS, Forsyth Institute, Cambridge, MA). Results: With the use of multi-dimensional scaling plots, support vector machine learning, odds ratio analysis, and other statistical methods, we have determined that treatment with povidone iodine can shift the composition of the salivary cariogenic microbiome to include higher proportions of aerobic microorganisms, such as Stentrophomonas maltophila, as well as non-cariogenic, anaerobic microorganisms including Poryphyromonas and Fusobacterium species. Conclusion: We have identified microorganisms that are associated with caries-active children and have determined that povidone iodine is an effective adjunctive therapy that has the potential to shift the composition of the cariogenic microbiome to one more closely aligned with non-cariogenic health.